Complex Permittivity and Microwave Absorption Properties of Zinc Oxide Leach Residues. (3rd September 2017) - Zhang, Weifeng; Luo, Zhumei; Chen, Junruo
ABSTRACT: Cylindrical cavity perturbation method was used to measure complex permittivity of zinc oxide leach residues (ZOLR) at frequency of 2.45 GHz. The results indicate that both dielectric constant and Loss factor of ZOLR increased with increased of temperature and moisture content. The research of ZOLR's microwave absorption properties were performed based on reflection loss (RL) theory. Microwave absorption peak of ZOLR moves towards higher material thickness with decreasing of moisture content. However, microwave absorption peak of ZOLR moves towards smaller material thickness with increasing of temperature. RL of ZOLR sensitively depends on material thickness of itself. If want to keeping microwave absorption properties of ZOLR greater than 90% in the process of microwave drying, 10 mm, 40 mm, and 50 mm should be selected as the optimum material thickness.